Mean-field and mean-ensemble frequencies of a system of coupled oscillators - Petkoski, Spase; Latsenko, Dmytro; Basnarkov, Lasko; Stefanovska, Aneta (American Physical Society, 2013)
We investigate interacting phase oscillators whose mean field is at a different frequency from the mean or mode of their natural frequencies. The associated asymmetries lead to a macroscopic travelling wave. We show that the mean ensemble frequency of such systems differs from their entrainment frequency. In some scenarios these frequencies take values that, counter-intuitively, lie beyond the limits of the natural frequencies. The results indicate that a clear distinction should be drawn between the two variables describing the macroscopic dynamics of cooperative systems. This has important implications for real systems where a non-trivial distribution of parameters is common.